ANALYSIS OF THE IMPACT OF INFRASTRUCTURE DEVELOPMENT ON MICRO, SMALL AND MEDIUM ENTERPRISES IN SEMPAKATA VILLAGE, MEDAN SELAYANG DISTRICT, MEDAN CITY - Royganda Siregar; Humaizi Humaizi; Zulkifli Zulkifli (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Infrastructure development has become a national priority aimed at strengthening the foundation of Indonesia’s economic growth. At the local level, particularly in Kelurahan Sempakata, Medan Selayang District, the 2023 road and drainage improvement projects were expected to enhance regional connectivity and stimulate economic activities among Micro, Small, and Medium Enterprises (MSMEs). However, such physical transformations also generate various social and economic challenges that require in-depth analysis. This study aims to analyze the social and economic impacts of road and drainage infrastructure development on MSME actors in Kelurahan Sempakata, as well as to identify the adaptation strategies they adopted in response to the new infrastructure. The analysis employs Jean-Paul Rodrigue’s Accessibility Theory and Hanson and Pratt’s Social Access Theory, emphasizing that accessibility encompasses not only physical connectivity but also social capability—the ability of economic actors to utilize emerging opportunities. The research applies a qualitative descriptive approach, using in-depth interviews, participatory observation, documentation, and literature review as data collection techniques. Informants include MSME owners from various sectors—trade, services, culinary, and workshops—as well as community leaders who represent the local socio-economic context. The findings reveal that infrastructure development has generated positive impacts, such as improved accessibility, enhanced distribution efficiency, and the emergence of new business opportunities. Nonetheless, during the construction phase, some MSMEs experienced income decline and operational disruptions due to limited customer access. After project completion, most MSME actors managed to adapt through service innovation, business restructuring, and product quality enhancement. The role of the local government in providing assistance and information dissemination proved essential in facilitating MSME adaptation.